1995
DOI: 10.1002/ajh.2830480105
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell rheology is determined by polymer fraction–not cell morphology

Abstract: Sickle cell disease pathophysiology is mediated by acute and chronic impairment of cell flexibility due to the formation of intracellular sickle hemoglobin (Hb S) polymer as cells are partially deoxygenated in the microcirculation. We have recently developed a method to measure the relationship between the formation of intracellular polymerized Hb S and cell filtration. In this study, we have used this method to examine whether sickle cell morphology, independent of Hb S polymer fraction, had an effect on cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
(25 reference statements)
2
14
1
2
Order By: Relevance
“…Shape change was found to be a reliable marker for cell sickling in hypoxia-induced sickled human RBCs at 37°C (36,37), although an earlier study argued otherwise based on experiments done at 24°C (47). Through imaging flow cytometry, the shape change was confirmed to be highly correlated with the existence of intracellular HbS polymers identified by transmission electron microscopy (TEM) in a recent study (37).…”
Section: Discussionmentioning
confidence: 97%
“…Shape change was found to be a reliable marker for cell sickling in hypoxia-induced sickled human RBCs at 37°C (36,37), although an earlier study argued otherwise based on experiments done at 24°C (47). Through imaging flow cytometry, the shape change was confirmed to be highly correlated with the existence of intracellular HbS polymers identified by transmission electron microscopy (TEM) in a recent study (37).…”
Section: Discussionmentioning
confidence: 97%
“…This type of result has already been observed in previous works (Brandao et al 2003;Monchanin et al 2005;Connes et al 2006, in press). It has been reported that RBCs from SCT carriers and subjects with SCA present impaired filtration in an oxygenated environment even with normal cell morphology, suggesting that cell morphology is not directly related to the abnormal rheological behavior (Hiruma et al 1995). Embury (2004) explained that with the passage from the arterial to the venous circulation substantial numbers of RBCs containing HbS become grossly sickled.…”
Section: Discussionmentioning
confidence: 98%
“…Mozzarelli et al [31] reported the presence of hysteresis between the sickling and unsickling curves of SS cells on the basis of the assumption that unsickling begins at a PO 2 of about 40 mmHg. We [1] and Hiruma et al [30] also showed that the PO 2 -dependent morphological changes of SS cells during oxygenation and deoxygenation significantly differ. We previously reported that the shape of fully deoxygenated SS cells depended on the rate of deoxygenation of oxygenated SS cells [16].…”
Section: Comparison Of the Properties Of Poscs And Pdscsmentioning
confidence: 98%
“…The existence of hysteresis between the sickling and unsickling curves of SS cells with respect to PO 2 has been reported [24,25,30]. Mozzarelli et al [31] reported the presence of hysteresis between the sickling and unsickling curves of SS cells on the basis of the assumption that unsickling begins at a PO 2 of about 40 mmHg.…”
Section: Comparison Of the Properties Of Poscs And Pdscsmentioning
confidence: 99%
See 1 more Smart Citation